DNA and modified vaccinia Ankara prime–boost vaccination generates strong CD8+ T cell responses against minor histocompatibility antigen HA‐1. (28th May 2021) - Eldershaw, Suzy A.; Pearce, Hayden; Inman, Charlotte F.; Piper, Karen P.; Abbotts, Ben; Stephens, Christine; Nicol, Samantha; Croft, Wayne; Powell, Richard; Begum, Jusnara; Taylor, Graham; Nunnick, Jane; et al.
Summary: Allogeneic immune responses underlie the graft‐ versus ‐leukaemia effect of stem cell transplantation, but disease relapse occurs in many patients. Minor histocompatibility antigen (mHAg) peptides mediate alloreactive T cell responses and induce graft‐ versus ‐leukaemia responses when expressed on patient haematopoietic tissue. We vaccinated nine HA‐1‐negative donors against HA‐1 with a 'prime–boost' protocol of either two or three DNA 'priming' vaccinations prior to 'boost' with modified vaccinia Ankara (MVA). HA‐1‐specific CD8 + T cell responses were observed in seven donors with magnitude up to 1·5% of total CD8 + T cell repertoire. HA‐1‐specific responses peaked two weeks post‐MVA challenge and were measurable in most donors after 12 months. HA‐1‐specific T cells demonstrated strong cytotoxic activity and lysed target cells with endogenous HA‐1 protein expression. The pattern of T cell receptor (TCR) usage by HA‐1‐specific T cells revealed strong conservation of T cell receptor beta variable 7‐9 (TRBV7‐9) usage between donors. These findings describe one of the strongest primary peptide‐specific CD8 + T cell responses yet recorded to a DNA–MVA prime–boost regimen and this may reflect the strong immunogenicity of mHAg peptides. Prime–boost vaccination in donors or patients may prove of substantial benefit in boosting graft‐ versus ‐leukaemia responses.